2018
DOI: 10.1098/rsos.181232
|View full text |Cite
|
Sign up to set email alerts
|

Acetophenone Mannich bases: study of ionic liquid catalysed synthesis and antioxidative potential of products

Abstract: Three-component Mannich reaction of acetophenone or 4-iodoacetophenone with a variety of substituted anilines and benzaldehyde, catalysed with diethanolammonium chloroacetate, was performed under mild conditions. Mannich bases (MBs), of which five are new, were obtained in good to excellent yields. All compounds were characterized using elemental analysis, NMR and IR. In addition, detailed experimental and simulated UV–Vis spectral characterization of these compounds is presented here for the first time. In vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…5,6 In addition to the aforementioned physical and chemical feature, ILs have an infinite variety of potential anion and cation choices and exchanges, leading to qualities like hydrophobicity, viscosity, density, solubility, and biodegradability that are specified and closely regulated. 7,8 It has many uses in the creation of functional materials 9 as well as chemical synthesis, 10 biomass conversion, 11 extraction, and separation. 12 In recent years, however, a growing body of research has revealed that the "green" is not true.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In addition to the aforementioned physical and chemical feature, ILs have an infinite variety of potential anion and cation choices and exchanges, leading to qualities like hydrophobicity, viscosity, density, solubility, and biodegradability that are specified and closely regulated. 7,8 It has many uses in the creation of functional materials 9 as well as chemical synthesis, 10 biomass conversion, 11 extraction, and separation. 12 In recent years, however, a growing body of research has revealed that the "green" is not true.…”
Section: Introductionmentioning
confidence: 99%
“…2 Due to their low reactivity and difficulties in restraining facial stereoselectivity, some enantioselective chiral catalytic C-C bond formation reactions with carbonyl are available, despite being effective procedures for enantioselective reduction of ketones. 3 In contrast, salen-metal complexes may be useful as bifunctional Lewis acid-base catalysts for contemporary catalytic reactions with imperative substrates. 4 Scientists have embraced Green Chemistry principles over the past few decades, and environmental considerations have become part of chemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…In medicine, mannich base and its derivatives are regarded as the best pharmacophore. [4][5][6] The phenolic mannich base, which has the structural components of a phenolic hydroxyl group and an aminoalkyl moiety, exhibits a wide range of biological activities, including anti-oxidant, anti-inflammatory, biometal chelating, anticholinesterase, and monoamino oxidase inhibitory properties. Apoptosis, cell cycle arrest, depolarization of the mitochondrial membrane and poorer topoisomerase-II inhibition were all a result of the mannich base's cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…According to functional group presence and activity relationships, the final analogs' antioxidant efficacies can be rated as follows: F > Cl > NO 2 > CH 3 > OCF 3 > CF 3 . Based on Gibbs free energy, an in vitro DPPH radical experiment revealed the molecule containing the anisidine moiety, 1-(4-iodophenyl)-3-((4-methoxyphenyl)amino)-3phenylpropan-1-one (55) has a superior radical scavenging activity 5,29.…”
mentioning
confidence: 99%